¿TUTORÍA O AUTORÍA? 1 - María das Graças TARGINO (Fonseca, Journal of Communication, 2023)
Over time, with the profound changes in the learning and in research provided by technological advances, and especially because of the extreme value of higher education and scientific research, there is an intense discussion around the old and worn slogan "publish or perish"